Design thinking as a perspective for the insertion of the university in the territory within the framework of integrality - Olivetti Espina, Mg. Lic. Miguel (Universidad Nacional del Litoral, 2019)
Design thinking as a theoretical-methodological perspective that arises in the academic field of design disciplines, through a series of attributes and tools allows re-thinking some integral university practices in the territory. Thinking about the role of the public university in the co-construction of the territorial dimensions, both at the conceptual level and in specific areas of intervention, requires a permanent analysis and critique for the generation of updated devices to the emerging problems of living in life daily of the territories. This article systematically presents some key conceptual positions on the articulation between the knowledge of design thinking, territory, and university approaches from an integral perspective of functions, disciplines and knowledge. Finally, the development of an intervention case in the University of the Republic of Uruguay, designed based on the previously discussed concepts, is presented.